DIMENSI NILAI TAUHID DALAM UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT: Undang-Undang Republik Indonesia Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Muhammad Miftahul Ikhsan (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
Religion has three main basics, namely faith, Islam and ihsan, discussion in faith is the value of tawhid, divinity. Islam teaches that religion is not only limited to worship, but can be applied in the aspect of living, by applying the principle of divinity, Ihsan in the sense of doing good deeds, is classified into 4 types, namely: doing good to Allah. This type of research uses literature research that takes data through information by obtaining library materials, data collection techniques for this research using documentation. data that has been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. tawhid is to worship God with the belief that God is the creator of the universe and all that it contains. Tawhid is divided into three types, namely tauhid rububiyah, tauhid uluhiyyah, tauhid asma' wa trait. The economic aspect of life does not escape the eyes of Allah, with regard to zakat, it is explained that zakat is to cleanse people. The perspective of the value of tawhid in the Law of the Republic of Indonesia Number 23 of 2011 concerning Zakat Management that this law takes the source that fulfilling zakat is the obligation of Muslims in accordance with the Qur'an. In chapter two which discusses the principles in zakat management such as Amanah, expediency, justice, legal certainty, integration and accountability. So in terms of tawhid asma' wa the nature of this principle is indeed part of tawhid because this principle is also included in asmaul husna like justice in asmaul husna al-adlu which is all just.